2023
DOI: 10.3390/agronomy13030615
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Inventory of Ethnobotanically Important Halophytes of North-Western Mediterranean Coastal Brackish Areas, Tuscany, Italy

Abstract: Plants have always been used by people for multiple purposes, but over the centuries knowledge of useful plants has largely been lost. Through ethnobotanical studies it is possible to retrieve information on the uses of plants and renew the ancient attention to plants which could be useful to apply in modern applications. In this context, the ethnobotanical use of halophytes has not been explored in depth. The present study focused on the flora of two brackish areas of the north-western Mediterranean sited in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 178 publications
0
5
0
Order By: Relevance
“…S. virginianum was extensively utilized by the local population in the study area. Upon reviewing previous literature, it was discovered that this plant had been traditionally employed for asthma, pain, and as a diuretic [ 43 ]. However, our current study revealed a novel use, indicating that it was employed in the treatment of liver problems in the study area .…”
Section: Resultsmentioning
confidence: 99%
“…S. virginianum was extensively utilized by the local population in the study area. Upon reviewing previous literature, it was discovered that this plant had been traditionally employed for asthma, pain, and as a diuretic [ 43 ]. However, our current study revealed a novel use, indicating that it was employed in the treatment of liver problems in the study area .…”
Section: Resultsmentioning
confidence: 99%
“…Other representative families are Brassicaceae, Poaceae, and Portulacaceae. They have been traditionally collected in the wild for human consumption and medicinal uses [13,14]. However, plant harvest in the wild (foraging) presents many risks due to possible microbiological and chemical contamination and appears to be incompatible with the quality and safety standards required by the current food market.…”
Section: Halophytes For Saline Agriculturementioning
confidence: 99%
“…Salicornia spp. is used as a vegetable and it is currently gaining increasing commercial interest; it is a halophyte species (i.e., it can tolerate high soil salinity concentrations) and it can be cultivated under very high soil salinity conditions [59][60][61]. Suaeda vera J. F. Gmel.…”
Section: The Species Under Studymentioning
confidence: 99%
“…The descriptions of these plant species in the literature are in perfect agreement with what was observed in our analysis, confirming all of their ecological characteristics and properties. Suaeda vera (S6), is a perennial halophyte commonly found in high to moderate salinity conditions; it has the ability to thrive in dry to very dry soils [60,61,88]. According to Sordes et al [89], Suaeda vera can be the dominant species, is able to recolonize silty salt sediments, and, together with other species, such as Salicornia sp., is a facilitator pioneer species in salt marsh succession.…”
Section: Plant Survey and Ecological Charactwrizationmentioning
confidence: 99%
See 1 more Smart Citation